CHARACTERISTICS OF MEANS AND PEDAGOGICAL CONDITIONS OF HEALTH CARE EDUCATION OF STUDENTS (ON THE BASIS OF THE WORKS OF UKRAINIAN AND POLISH SCIENTISTS) - Slyvka, Larysa (Mountain School of Ukrainian Carpaty, 2022)
The article states that the definitions of the term «health education» in the Ukrainian scientific pedagogical space are vague and somewhat vague. The functional and structural means and pedagogical conditions of health education are singled out. The content and forms and methods of the specified pedagogical process are considered in the research by means of practical implementation of health education. The pedagogical conditions include a set of measures that are created consciously to ensure the greatest effectiveness of health education, namely: theoretical and methodological training of teachers to implement the appropriate educational impact; interaction and cooperation of different subjects of education. Functional and structural means and pedagogical conditions of health education (HE) are united into four groups: semantic dimension of HE; technological dimension (methods and forms) HE; subject-institutional dimension of HE; professional and competence dimension of HE. Each of the measurements is briefly described. It is determined that the content of education is a set of knowledge, skills and abilities that must be acquired in the process of studying the basics of science. Reflections of educational content are curricula, programs of academic disciplines, educational programs, special educational and methodical materials. The content of health education is quite extensive: it covers all dimensions of health physical, social, mental, spiritual. The technological dimension (forms and methods) of health care is related to the need to form in students the appropriate views and beliefs that can become the core of behavior to maintain health. The determining factor in the effectiveness of health education is the availability of qualified professionals. The most important area for the implementation of health education is the school, but the success of educational effects on health is directly related to the broad involvement in the educational process of various state and public structures. Keywords: health education, pedagogical conditions, means of education, works of Ukrainian and Polish scientists.